Design and Analysis of Ejector Pin in The Oil Seal Mould to Improve Its Mechanical Properties - Haris Wahyudi; Swandya Eka Pratiwi; Irwan Firdaus (Institute for Research on Innovation and Industrial System (IRIS), 2020)
Ejector pin in the mould is used to release (eject) the finished product, to vent gas out of the cavity and to expedite the material flow. It must have high strength, good hardness, good wear and corrosion resistance to withstand high pressure. Poor ejector pin may result in defect of finished product and delay the process due to additional time was required to release sticking product in the mould. The aim of this research is to select proper material for the ejector pin and analyse it not to experience plastic deformation. Three specimens’ steel was considered for making the pin, SUS 304, normal SKS 3 and heat treated SKS 3. Hardness and tensile test were used to examine the mechanical properties of specimens and impact was utilized to obtain impact energy using Charpy method. Static stress analysis was also used to simulate the working load using SolidWorks. Rockwell hardness test recorded that SUS 304, normal SKS 3 and heat treated SKS have 23.2 HRC 9.6 HRC and 38.03 HRC, respectively. Tensile test produced yield strength of 452.9 MPa for SUS 304 and 432.6 MPa for SKS 3. Impact energy absorbed during Charpy test for SUS 304 equal to 0,804 J/ mm2 and specimen SKS 3 equal to 0,863 J/mm2. By taking the mechanical test result and SolidWorks simulation, it was concluded that the suitable material for ejector pin is SUS 304.